Are patients whose study partners are spouses more likely to be eligible for Alzheimer’s disease clinical trials? - Grill, Joshua D. (2012)
BACKGROUND/AIMS: Alzheimer’s disease (AD) clinical trials enroll two participants: a patient and a study partner. The primary caregiver most often fills the role of study partner and most trial study partners are spousal caregivers. METHODS: AD trial inclusion criteria were applied to baseline data from 5674 probable AD dementia research participants in the National Alzheimer’s Coordinating Center Uniform Data Set. Eligibility was compared among patients with spousal, adult child, and other types of study partners. RESULTS: Patients with spousal study partners were more frequently eligible than patients with adult child study partners. Compared to patients with spousal study partners, patients with adult child study partners were more frequently ineligible because of age, residence in skilled nursing facility, excluded low scores on the MMSE, excluded high score on Hachinski ischemia scale, and failure to fulfill a minimum number of weekly visits with the study partner. CONCLUSIONS: In this sample, patients with adult child study partners were less likely to qualify for AD clinical trials than were patients with spousal study partners. This may contribute to the lower representation of patients with adult child caregivers in these studies.